A Hill Full of Points in Terra Incognita from Patagonia: Notes and Reflections for Discussing the Way and Tempo of Initial Peopling - Miotti, Laura Lucia (2015)
We present the environmental and archeological results of research at Cerro Amigo Oeste, a mesa-top archeological site with Fishtail points located on the Somuncurá Plateau, northern Patagonia, Argentina. Comparison with other South American sites is used to interpret archeological landscapes of colonization. The objects, features, and beings of landscape are understood as reflecting the materiality of social relations as well as patterns of production, retooling, and mobility. Cerro Amigo Oeste is in a very special location due to its high elevation and extensive view of the landscape, as well as its archeological and ethnographic significance. It can be considered a node or hub of communication in the social network among hunter-gatherers far and near in the late Pleistocene